Rheology of the Cu-H2O nanofluid in porous channel with heat transfer: multiple solutions - Raza, J.; Mohd Rohni, Azizah; Omar, Zurni; Awais, Muhammad (Elsevier B.V., 2017)
Dynamics of nanofluid comprising a base fluid (water) with copper (Cu) nanoparticles have been considered in channel with porous walls under magnetic field influence. The channel walls are considered to be permeable in order to analyze the wall mass transfer phenomenon. Relevant mathematical modelling has been performed and the derived PDEs are converted into coupled nonlinear ODEs by using suitable transformations. Computations have been made numerically by employing the shooting technique. It is noted that multiple solutions occur for the variation of suction Reynolds number, solid volume fraction and magnetic parameters which are interpreted in detail.